Social Media Literacy Training for Preventing Cyberbullying Intention among Senior High School Students - Prihastuty, Rahmawati; Swaraswati, Yogi; Rahmawati, Dyah Ayu; Dzakiyyatul, Siti Nur (Universitas Muhammadiyah Surakarta, 2019)
Purpose: This study aimed to determine the effectiveness of social media literacy training on prevention of cyberbullying in high school students Methodology: This study used the experiment method, with one pretest-posttest group design. The treatment applied was social media literacy training to prevent cyberbullying for a day. Thirty high school students who were members of OSIS participated in this study. This selection was the first step to form an anti-cyberbullying agent. The participants were picked using a purposive sampling technique. Data were collected using two instruments, knowledge test of cyberbullying and the cyberbullying intention scale. Then, the data were analyzed using a non-parametric Wilcoxon signed-rank test with the assist of data processing software. Results: Research result revealed that the Z score for pretest-posttest of students’ knowledge on cyberbullying was -4.801 with p = 0.00 (p < 0.01). In addition, the result of pretest-posttest of cyberbullying intention shows Z score -4.792 with p = 0.00 (p < 0.01). The conclusion is the level of cyberbullying knowledge increases, and cyberbullying intention reduce after training; thus, the hypothesis accepted.Applications/Originality/Value: Social media literacy training is sufficient to prevent cyberbullying in high school students. Prevention and intervention efforts regarding the increase of cyberbullying knowledge and reduce cyberbullying intention discussed further.